INDEPENDENT WORK OF STUDENTS AS A MEANS PERSONALITY FORMATION (Pedagogy of Higher and Secondary Education, 2007)
The article is devoted to forming of student's personality by facilities of independent educational activity on the modern stage of educational development in higher educational establishments. Problems of students' independent work which appear the process of educational activity influence on forming of personality.